Performance of thermoplastic composite tubular structures - Tan, Kian Cheow (Nanyang Technological University, 2021)
As the demand for use of composite hollow structures is growing in aerospace, automobile and extensively in sporting industries etc., there is a need to study on materials and manufacturing methods to achieve composites with improve mechanical properties and efficiency in manufacturing. Polypropylene fiber has come into attention in the composite with superior performance characteristics like impact and vibration damping and being relatively cheaper and lighter than the widely used carbon and glass fabrics. However, they are lower in stiffness and strength and hence are not suitable to be directly used for industrial applications requiring higher specific properties apart from the impact. Hence, hybridisation of carbon and polypropylene might be an interesting solution to explore. Together with novel acrylic thermoplastic resin which can improve overall properties of composite structure. Manufacturing complex parts through prepreg is usually costly, hence this project looked into resin injection method to significantly which reduce the cost of production. Innegra polypropylene fabric with thermoplastic Elium® resin have been fabricated using Bladder-assisted Resin Transfer Moulding. The structures have achieved desired fiber volume fraction and thickness with good surface finish. Subsequently, vibration, flexural and impact tests have been conducted on the tubular composite structures and damage observation done under microscopy. Hybrid carbon polypropylene tubular composite structure has shown positive results in comparison with pure woven carbon and Innegra polypropylene configurations. Mechanical properties such as strength and stiffness showed significant improvement. Natural frequency fluctuates within 85-95Hz which is less than 1% and % structural damping between 4-5%, these results indicate uniformity along the hybrid tubular composite structure. The hybrid composite took a peak load of 1.38kN with no signs of catastrophic failure. During impact testing, the hybrid tubular composite displayed minimal failure on flange and web up till 21.5 J impacted energy together with little deformation. In addition, there were lesser failures observed in the cross-section under microscopy.